Helping hands : a radio documentary profiling the work of the male nurse. - Ow, Kylie Siak Wei. (2009)
The state of health in Singapore is good by international standards. However, the ageing population may require better and more healthcare services from the various healthcare institutions to satisfy their medical needs. Having anticipated this situation, it will imply that Singapore will need to cultivate more healthcare professionals such as nurses to cope with the increasing health demands of old age. With this concern in mind, this paper aims to provide a general overview of nursing in Singapore, with its focus on male nurses. It will then determine whether there is a rising trend among males to join this female dominated profession before explaining the possible reasons for the trend. Since the audio project contains a dramatic feature on two male nurses from the Philippines who respond to medical emergencies on motorcycles, this paper will also touch on a similar service provided by the Singapore Civil Defense Force.